2015
DOI: 10.3109/15622975.2015.1019359
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and electrophysiological markers of pragmatic language comprehension in schizophrenia

Abstract: Our results indicate group differences in cortical electrophysiological and haemodynamic activation that represent rather general impairments in the processing of complex language. Simultaneous EEG/NIRS applications are useful to depict these neural markers and to investigate their relationship. Future studies are needed to clarify the nature of respective anomalies and their potential as putative neural markers in schizophrenia research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Miscomprehension of figurative meanings by schizophrenic patients is a phenomenon already mentioned in historical descriptions (Hadlich, 1931 ; Goldstein, 1939 ; Kasanin, 1944 ; Elmore and Gorham, 1957 ). The deficit includes all subtypes of figurative language including proverbs (Brattemo, 1962 ; Rapp et al, 2014 ), metaphors (Langdon et al, 2002 ; Schneider et al, 2015 ; Bambini et al, 2016a ), irony (Sparks et al, 2010 ; Rapp et al, 2013 , 2014 ), and idioms (Titone et al, 2002 ; Schettino et al, 2010 ; Sela et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Miscomprehension of figurative meanings by schizophrenic patients is a phenomenon already mentioned in historical descriptions (Hadlich, 1931 ; Goldstein, 1939 ; Kasanin, 1944 ; Elmore and Gorham, 1957 ). The deficit includes all subtypes of figurative language including proverbs (Brattemo, 1962 ; Rapp et al, 2014 ), metaphors (Langdon et al, 2002 ; Schneider et al, 2015 ; Bambini et al, 2016a ), irony (Sparks et al, 2010 ; Rapp et al, 2013 , 2014 ), and idioms (Titone et al, 2002 ; Schettino et al, 2010 ; Sela et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…SZ patients exhibited a de¯ciency in understanding complex language as they displayed incomplete and delayed comprehension, which leads to impaired activation patterns. 216…”
Section: Language Comprehensionmentioning
confidence: 99%
“…Schizophrenic patients (SP) show a tendency of concretism in their comprehension of figurative language (Schneider et al, 2015). It means they tend to choose literal meaning when they interpret figurative language.…”
Section: Behavioral Approachmentioning
confidence: 99%
“…Meanwhile, they found SPs' left precuneus cortex had higher activation in both novel condition and literal condition. Schneider et al (2015) used ERPs-NIRs technique to look into SPs' metaphor comprehension. They found that SPs' left frontal gyrus, left temporo-parietal junction (lTPJ), right inferior gyrus had lower activation under all conditions.…”
Section: Lateralizationmentioning
confidence: 99%
See 1 more Smart Citation